Nisza rynkowa jako alternatywna strategia rozwoju małych przedsiębiorstw - Jasiński, Bartosz (Market Niche as An Alternative Development Strategy of Small Enterprises, 2006)
The author in this article tries to show a possible basis of future grow for the small and middle firms on the polish market. Points that a very good basis of competitiveness for that kind of firms could be innovations (originality of products and models of business) and tradition, local patriotisms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 443-449